2017
DOI: 10.1002/mrm.27004
|View full text |Cite
|
Sign up to set email alerts
|

Error analysis of helmholtz‐based MR‐electrical properties tomography

Abstract: The numerical error introduced by the computation of spatial derivatives using FD kernels is one of the major causes of limited accuracy in Helmholtz-based MR-EPT reconstructions. Magn Reson Med 80:90-100, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 42 publications
0
85
0
Order By: Relevance
“…DL-EPT differs significantly from conventional MR-EPT techniques employing analytical or algebraic reconstruction models. The popular Helmholtz MR-EPT technique, an example of an analytical reconstruction technique, requires the computation of spatial derivatives on measured data 14 . This computation is performed by convolving the measured, complex ̃ field with large finite difference kernels such as the 3D kernel adopted in this work 11 , or the Savitzky-Golay kernel 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DL-EPT differs significantly from conventional MR-EPT techniques employing analytical or algebraic reconstruction models. The popular Helmholtz MR-EPT technique, an example of an analytical reconstruction technique, requires the computation of spatial derivatives on measured data 14 . This computation is performed by convolving the measured, complex ̃ field with large finite difference kernels such as the 3D kernel adopted in this work 11 , or the Savitzky-Golay kernel 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Spatial derivatives are computed by applying a filter (in this case a 2 nd order finite difference filter) to the ̃ field data, resulting directly in EPs maps. However, this operation is highly sensitive to the intrinsic noise in the MR measurements, and consequently the reconstructed EPs maps lack precision 13,14 . To mitigate the impact of noise in the reconstructed EPs maps, large derivative filters in combination with image filters and large voxel sizes are commonly used 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In MREPT, the modification of the Laplacian operator has been investigated previously for noise-robust conductivity imaging. 14,18 In these previous studies, several discrete Laplacian operators were suggested to reduce noise power by combining adjacent kernels. In this work, distant-dependent weightings were applied to each Laplacian operator to manipulate the envelope.…”
Section: Discussionmentioning
confidence: 99%
“…For all simulations and experiments, prefiltering that reduces phase errors due to Gibb’s ringing was applied to the raw B1+ and MR data using an isotropic Gaussian kernel with 2.0 × 2.0 mm 2 FWHM. The SD was determined as FWHM/( res ⋅2ln2), for which FWHM represents the full‐width half‐maximum in units of mm, and res represents the resolution in units of mm.…”
Section: Methodsmentioning
confidence: 99%
“…Standard Helmholtz-based EPT (MR-EPT) [8]requires a constant dielectric profile and second-order spatial differentiation of the data. Care must be taken when implementing this differentiation operation to mitigate noise amplification [3], [15], [16]. On the other hand, in the global integral-based approach the dielectric tissue parameters are determined in an iterative manner by minimizing an objective function.…”
Section: Introductionmentioning
confidence: 99%